Writing Interventions for Individuals with Autism Spectrum Disorder: A Research Synthesis. - Accardo, Amy L.; Finnegan, Elizabeth G.; Kuder, S. Jay; Bomgardner, Estyr M. (Journal of Autism & Developmental Disorders, 2020)
Building on previous research in the area of written expression for individuals with ASD a research synthesis was conducted to identify (1) writing interventions that have been studied and their effect in improving writing skills of individuals with ASD, (2) intervention features that influence the writing skills of learners with ASD, and (3) the quality of the research. A total of 62 participants were represented across the 24 single case design studies meeting inclusion criteria. Nine interventions emerged with a majority focused on self-regulated strategy development. Effective interventions (PND above 70%) are reported, along with the emergent feature of "packages" using co-occurring combinations of visual, motivational, choice, technology, behavioral, peer, auditory, and tactile supports in conjunction with writing interventions.